Willow CM pulps for newsprint: II. Relationships between wood characteristics and pulp properties - Monteoliva, Silvia Estela (2008)
The aim of this work was to establish relations, through multiple regressions, that allow the prediction of the properties of CMP pulp from willows for newsprint, from the viewpoint of wood characteristics. Another objective was to verify whether the traditional factors used to characterize softwood mechanical pulps are still applicable to hardwood chemimechanical pulps. Linear and quadratic multiple regression models were evaluated by the results of a previous work, on the chemimechanical pulping of six willow clones (Salix sp) from two different plantation sites. The variables measured on wood, considered as independent variables, were the following: basic density, fiber length, fiber width, cell wall thickness, lumen width, moisture content, hot water and alcohol-benzene extractive content, total extractives, soluble materials in 1% sodium hydroxide, insoluble, soluble and total lignin, and cellulose content of wood. The independent pulp variables were fractions of MacNett classification, Forgacs’ “L” factor, intrinsic fiber strength (measured by zero span tensile test), water retention value (WRV) and pulp drainability (°SR). The dependent variables used were specific volume, tear and tensile index, brightness, opacity, light scattering coefficient (s) and light absorption coefficients of handsheets (k). The best fit models were obtained by considering fiber fractions and pulp weakening and, to a lesser extent, the properties of wood. Therefore, one could reasonably predict numerous chemimechanical pulp properties that could be used as a first selection criterion for obtaining clones for pulp with better mechanical and optical properties.